2003
DOI: 10.1002/jcb.10524
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1‐induced vascular smooth muscle cell chemotaxis: The role of the type 3 repeat and carboxyl terminal domains

Abstract: Thrombospondin-1 (TSP-1), an acute phase reactant implicated in vascular disease, is a matricellular glycoprotein with six domains that confer different functions. The authors have shown TSP-1 induces vascular smooth muscle cell (VSMC) chemotaxis via extracellular signal-regulated kinases-1 and -2 (ERK) and p38 kinase (p38) and that a fusion protein of the carboxyl terminal (COOH) and type 3 repeat (T3) domains independently induce VSMC chemotaxis. The purpose of this study was to determine whether COOH-, T3-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The conformation of TSP1, therefore, may influence neointima formation through altering its interactions with versican and potentially other ECM components. However, TSP1 also interacts with several receptors on VSMC and thereby has direct effects on HASMC proliferation and migration (Isenberg et al, 2005;Lee et al, 2003;Lymn et al, 2002;Yabkowitz et al, 1993). Thus, TSP1 bound to versican on microfibrils may alter VSMC responses by providing prolonged stimulation of TSP1 receptors on these VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…The conformation of TSP1, therefore, may influence neointima formation through altering its interactions with versican and potentially other ECM components. However, TSP1 also interacts with several receptors on VSMC and thereby has direct effects on HASMC proliferation and migration (Isenberg et al, 2005;Lee et al, 2003;Lymn et al, 2002;Yabkowitz et al, 1993). Thus, TSP1 bound to versican on microfibrils may alter VSMC responses by providing prolonged stimulation of TSP1 receptors on these VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, IL-4 TSP-1 -EC: 1expression of cell adhesion molecules (189) No data available -VSMC: stimulation of chemotaxis (147,191) -1Aggregation and stability of platelet aggregates (188) ACS, acute coronary syndrome; bFGF, basic fibroblast growth factor; CAD, coronary artery disease; CRP, C-reactive protein; EC, vascular endothelial cells; eNOS, endothelial nitric oxide (NO) synthase; IGT, impaired glucose tolerance; IMT, intima-media thickness; iNOS, inducible NO synthase; MMP, matrix metalloproteinase; oxLDL, oxidized low-density lipoprotein; ROS, reactive oxygen species; T2DM, type 2 diabetes mellitus; VSMC, vascular smooth muscle cells.…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 99%
“…Thrombospondin-1 (TSP-1) is a member of a protein family that mediates cell-matrix and cell-cell interactions. Experimental data have shown that TSP-1 stimulates the aggregation and stability of platelet aggregates (188), induces the expression of cell adhesion molecules (189) in endothelial cells, and stimulates chemotaxis in vascular SMCs (147,191). In TSP-1 knockout mice, more extensive postinfarction remodeling has been observed compared with wild-type mice (72).…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 99%
“…Besides its antiangiogenesis efficacy, thrombospondin-1 activates latent TGF-h and suppresses tumor cells that respond to TGF-h inhibition (16). However, thrombospondin-1 is a complex macromolecule (450 kDa) with numerous other receptors, and its use may be clinically limited because of its size, difficulty in large-scale production, and more importantly, concerns about side effects that might result from its multiple other biological functions, such as the induction of vascular smooth muscle cell chemotaxis by the type 3 repeats and COOH-terminal domains (25). The antiangiogenic domain of thrombospondin-1, 3TSR, provides a promising alternative for clinical administration, because both antiangiogenic and TGF-h activation (KRFK) sequences are located within 3TSR (16).…”
Section: Introductionmentioning
confidence: 99%